The historical phonology of Paunaka (Arawakan) - Carvalho,Fernando O. de (2018)
Abstract This paper applies the comparative method to unravel the historical development of the segmental phonology of Paunaka, an Arawakan language of Bolivia. Although the Paunaka vowel system features a single back rounded vowel, it is rather simple to show that it derives from a system with two back rounded qualities *u and *o, but that the former segment shifted to a high central unrounded vowel ɨ. The language has lost *r unconditionally, implying that Paunaka items with r are probable loanwords. Paunaka underewent a spirantization of *ts, thus merging this affricate with the fricative *s. Although Paunaka shares a coronalization of *k > s with Proto-Mojeño, most of the phonological developments that affected Paunaka are either recurrent in the Arawakan language family or only superficially similar to developments in related languages, and thus provide little weight as evidence for subgrouping. An Appendix is also included, with 105 etymologies matching Paunaka lexical and grammatical morphemes with their cognates in Proto-Mojeño, the two extant Mojeño dialects (Ignaciano and Trinitario) and Terena.